Dining in Tuva: Social correlates of diet and mobility in Southern Siberia during the 2nd–4th centuries CE. Issue 1 (7th March 2022) - Milella, Marco; Caspari, Gino; Laffranchi, Zita; Arenz, Gabriele; Sadykov, Timur; Blochin, Jegor; Keller, Marcel; Kapinus, Yulija; Lösch, Sandra
Abstract: Objectives: Contemporary archeological theory emphasizes the economic and social complexity of Eurasian steppe populations. As a result, old notions of "nomadic" cultures as homogenously mobile and economically simple are now displaced by more nuanced interpretations. Large part of the literature on diet and mobility among Eurasian pastoralists is focused on the Bronze and Iron Ages. The underrepresentation of more recent contexts hampers a full discussion of possible chronological trajectories. In this study we explore diet and mobility at Tunnug1 (Republic of Tuva, 2nd–4th century CE), and test their correlation with social differentiation. Materials and Methods: We compare demographic patterns (by age‐at‐death and sex) of carbon, nitrogen, and sulfur stable isotope ratios (δ 13 C, δ 15 N, and δ 34 S) among 65 humans and 12 animals from Tunnug1 using nonparametric tests and Bayesian modeling. We then compare isotopic data with data on perimortal skeletal lesions of anthropic origin and funerary variables. Results: Our analyses show that: (1) diet at Tunnug1 was largely based on C4 plants (likely millet) and animal proteins; (2) few individuals were nonlocals, although their geographic origin remains unclarified; (3) no differences in diet separates individuals based on sex and funerary treatment. In contrast, individuals with perimortal lesions show carbon and nitrogen stable isotope ratios consistent with a diet incorporating a lower consumption of millet and animal proteins. Discussion: Our results confirm the previously described socioeconomic variability of steppe populations, providing at the same time new data about the economic importance of millet in Southern Siberia during the early centuries CE.